Strategi E-Business Berkelanjutan: Pendampingan UMKM Desa Cibadung dalam Mengembangkan Model Bisnis Digital - Pramono, Nugroho Heri; Wulandari, Provita; Surahman, Hendy (Jurnal Abdi Negeri, 2025)
This community service program aims to enhance the digital capacity of Micro, Small, and Medium Enterprises (MSMEs) in Cibadung Village through a sustainable e-business strategy. The initiative is based on the low adoption of digital technology among rural MSMEs, which results in limited efficiency, market reach, and business competitiveness. The program was implemented in three main stages: identifying MSME needs through field surveys; conducting interactive training on the use of financial applications, digital marketing strategies, and efficient production tools; and evaluating the program’s impact through pre-tests, post-tests, and the establishment of a WhatsApp-based digital community. The results indicate that the program had a significant impact in three key areas. First, business efficiency improved as 60% of participants began using digital accounting applications, saving 2–3 hours of operational time per day. Second, 75% of participants reported increased visits and transactions via social media and online marketplaces. Third, the creation of a digital community among MSME actors encouraged ongoing information exchange, consultation, and collaboration. The program demonstrates that a needs-based approach, contextual training, and multi-stakeholder collaboration can effectively accelerate inclusive technology adoption. It is expected that this initiative can serve as a pilot model for village-based MSME digital transformation and be replicated in other regions using a similar approach to foster sustainable local economic growth.